2006
DOI: 10.1890/0012-9658(2006)87[1289:aomtst]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of 54 Moist-Forest Tree Species: Traits, Trade-Offs, and Functional Groups

Abstract: Tree architecture is an important determinant of the height extension, light capture, and mechanical stability of trees, and it allows species to exploit the vertical height gradient in the forest canopy and horizontal light gradients at the forest floor. Tropical tree species partition these gradients through variation in adult stature (Hmax) and light demand. In this study we compare 22 architectural traits for 54 Bolivian moist-forest tree species. We evaluate how architectural traits related to Hmax vary w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
476
3
17

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 451 publications
(525 citation statements)
references
References 46 publications
29
476
3
17
Order By: Relevance
“…1999; Poorter et al. 2006). An alternative explanation to competition as the main internal filtering process is that community‐scale internal filtering is nonrandomly affected by site‐specific species (Baldeck et al.…”
Section: Discussionmentioning
confidence: 99%
“…1999; Poorter et al. 2006). An alternative explanation to competition as the main internal filtering process is that community‐scale internal filtering is nonrandomly affected by site‐specific species (Baldeck et al.…”
Section: Discussionmentioning
confidence: 99%
“…Such a strategy is especially beneficial for shade-tolerant species that regenerate in the light-limited understory. Indeed, several other studies also found that shade-tolerant species make wider crowns (Sterck et al 2006;Poorter et al 2006). In contrast, branches made of low-density wood are weaker, and need therefore to be extra thick to provide sufficient strength (Sterck et al 2006).…”
Section: Wood Densitymentioning
confidence: 97%
“…Alternatively, no clear asymptote is found because mature undisturbed pine forests are rare in the Mediterranean. Although it is generally assumed that height-diameter relationships should be asymptotic, studies from different forests show that a quarter of the species evaluated do not show such an asymptotic relationship (Thomas 1996;Chave et al 2003;Poorter et al 2006; but also see Aiba and Nakashizuka 2009). Species that do show an asymptote are canopy species from closed forest types, or species from more open woodland.…”
Section: Tree Heightmentioning
confidence: 99%
“…Four species (Cedrela, Sterculia, Tabebuia and Hura) have been described in many studies as long-lived shadeintolerant species but not pioneers (Welden et al 1991;Poorter and Hayashida-Oliver 2000;Kitajima 2002;Poorter et al 2006). They are characterised by intermediate growth rates at the seedling stage (see Wright et al 2003) (with the exception of Cedrela, which presents a high growth rate, see Menalled and Kelty 2001) and by seed dry masses above 0.01 g. From these four species, Tabebuia is markedly the most shade tolerant with a d.s.…”
Section: Species Selection Plantation Establishment and Early Measurmentioning
confidence: 99%
“…Most previous studies analysing survival, establishment and growth patterns of native tropical species (e.g. Condit et al 1996a;Welden et al 1991;Poorter 2006) have been conducted in forest conditions, which can differ considerably from the environment characteristic of open-grown plantations.…”
Section: Introductionmentioning
confidence: 99%